Building a Next-Gen SOC with IBM QRadar accelerate your security operations and detect cyber threats effectively - Kothekar, Ashish M.; Patil, Sandeep 20. Jh (Packt Publishing, 2023)
Are you looking for a QRadar guide that can help you to build a very efficient SOC for Threat Hunting, need-to-know software updates, or understanding compliance and reporting? Then this one-stop guide will help you to understand everything about IBM QRadar, and how it stores network data in real-time. This book will start with a quick introduction to QRadar components and architecture, and you will learn different ways to deploy the QRadar. It is important to be aware of the major and minor upgrades that take place in software hence you will learn how to scale, upgrade, and maintain QRadar. Once you get a detailed understanding of QRadar and how its environment is built, it is time to understand what all features can be used as per the business requirements, you will learn about Events, Flows, and searches through examples. As you advance, you will explore predefined QRadar applications and extensions that mine the data successfully and you would be integrating AI in Threat Management with confidence. Towards the end of this book, you will create and understand different types of apps in QRadar, troubleshoot and maintain it, and understand the current security challenges and address them through QRadar XDR. By the end of this book, you'll be able to apply IBM Qradar SOC's prescriptive practices and leverage its capabilities to build a very efficient SOC in your enterprise.